Strategi Etnik Jawa Dalam Pemanfaatan Sumber Daya Alam - Ella Anggraini; Nadila Roselani; Syaidatul Azhari; Nuriza Dora (JOURNAL SAINS STUDENT RESEARCH, 2025)
This research examines Javanese ethnic strategies in utilizing natural resources, which are based on local wisdom, cultural values and social norms that have been passed down from generation to generation. In the view of Javanese society, the environment is considered an integral part of life that must be maintained in balance. The principle of harmony with nature is realized through various traditional practices, such as terraced farming systems, crop rotation, and collective management of water resources. In addition, the value of mutual cooperation is an important basis for managing resources, creating a communal-based system that strengthens community solidarity. This approach not only involves sustainable use of natural resources, but also conflict resolution through deliberation and consensus, prioritizing inclusive social dialogue. In facing modernization, Javanese people are able to combine technological innovation with local wisdom to increase the efficiency of resource management without destroying the ecosystem. A concrete example of this adaptation can be seen in agricultural land management which combines organic techniques with modern irrigation technology. The results of this research show that these strategies not only support environmental sustainability but also strengthen the social and economic resilience of communities. This study underlines the importance of integration between tradition and innovation in creating adaptive and sustainable natural resource management models. These findings make a significant contribution to the development of culture-based policies for managing natural resources at local and national levels.